(untitled) (New York, 1999)
This book offers, in a standardizedand readily accessible tabular format, concise information on the syntheses, structures, properties, and applications of the most important polymetric materials. Considerable thought was given to the criteria for selecting the polymers included in this book. The first criterion was current commercial importance - the use of the polymer in commercial materials - for example, as a thermoplastic, a thermoset, or an elastomer; or more purposes. The second criterion was novel applications - a polymer that is promising for one or more purposes but not yet of commercial importance - for example, because of its electrical conductivities, its nonlinear optical properties, or its suitability as a preceramic polymer. Finally, the book includes some polymers simply because they are unusually interesting - for example, those utilized in fundamental studies of the effcts of chains stiffness, self-assembly, or biochemical processes.
Keywords: chemistry, organic,polymer